Syngas-based annex concepts for chemical energy storage and improving flexibility of pulverized coal combustion power plants. (15th October 2015) - Wolfersdorf, Christian; Boblenz, Kristin; Pardemann, Robert; Meyer, Bernd
Highlights: Annex concepts with coal gasification and synthesis unit linked to PCPP. Capital costs reduced by 21% because of shared infrastructure with PCPP. Annex improves flexibility of existing power plants. Integration of green power with annex concepts by optional electrolysis. Abstract: The increasing supply of fluctuating power from renewable sources not only in Germany requires improved capability for part load operation of conventional power plants in combination with electricity storage solutions to ensure the security of electricity supply. Different operational concepts are introduced to link a base load lignite-fired power plant with a small sized coal gasification and synthesis unit (annex unit). The annex unit comprises coal gasification, water electrolysis (optional), gas treatment and subsequent synthesis of storable fuels or chemicals (SNG, methanol). This unit is a power sink and chemical energy storage in times of renewable excess electricity, which reduces the overall net power output to the grid and lifetime-consuming start-ups and shutdowns of the power plant. In addition, the annex unit can also provide peak load in line with the actual demand. The concepts are modeled and evaluated regarding efficiency, CO2 emissions and the ability to reduce the minimal load of the total plant. The study was performed for an annex unit with 500 MW(th) gasifier linked to a 2264 MW(th) power plant. As a result, the annex concept with an additional 150 MW(el) electrolysis unit can reduce the power output to the grid from 50% minimal load to 33–34% during "electricity storage" and can increase the power output to the grid from 100% nominal load to 152–154% during "peak load generation". The improved flexibility of the annex concepts is accompanied by a reduction of the total efficiency (power plant and annex with re-combustion of the produced fuel) and a subsequent rise of the specific CO2 emissions. Thermal efficiencies of annex concepts without electrolysis result in 63.1% for SNG and 55.5% for methanol. The capital expenditure of an annex unit (without electrolysis) is 21% lower than for an equally sized stand-alone unit because of taking advantage of the shared infrastructure of the coupled power plant. Despite the growing share of green power there will be a significant demand for base load. The introduced annex concepts can contribute to flexibility and economics of existing conventional coal-fired power plants.